2014
DOI: 10.1080/02699931.2014.985188
|View full text |Cite
|
Sign up to set email alerts
|

The role of current affect, anticipated affect and spontaneous self-affirmation in decisions to receive self-threatening genetic risk information

Abstract: One reason for not seeking personally threatening information may be negative current and anticipated affective responses. We examined whether current (e.g., worry) and anticipated negative affect predicted intentions to seek sequencing results in the context of an actual genomic sequencing trial (ClinSeq®; n = 545) and whether spontaneous self-affirmation mitigated any (negative) association between affect and intentions. Anticipated affective response negatively predicted intentions to obtain and share resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…When asked whether they "avoid visiting their doctor even when they suspect they should [visit]," 40.4 percent of those under fifty and 29.4 percent of those over fifty said they did so. Ferrer et al (2015) 7 Consistent with this prediction, Emanuel et al (2015) find that, against the backdrop of 39 percent of survey respondents who reported that they would "rather not know [their] chance of getting cancer," those who believed that there isn't much one can do to prevent cancer were more likely to not want to obtain the information.…”
Section: Anxietysupporting
confidence: 57%
See 1 more Smart Citation
“…When asked whether they "avoid visiting their doctor even when they suspect they should [visit]," 40.4 percent of those under fifty and 29.4 percent of those over fifty said they did so. Ferrer et al (2015) 7 Consistent with this prediction, Emanuel et al (2015) find that, against the backdrop of 39 percent of survey respondents who reported that they would "rather not know [their] chance of getting cancer," those who believed that there isn't much one can do to prevent cancer were more likely to not want to obtain the information.…”
Section: Anxietysupporting
confidence: 57%
“…They find that neither the base rate nor the diagnosticity have an effect on the proportion of people who would like to avail themselves of the test, perhaps because the two effects involving worry and hope operate in opposing directions, or perhaps because the preference is largely driven by powerful heterogeneity in personal preferences. However, much as in Ferrer et al (2015), the potential for treatment does have a big effect; the proportion of people willing to get tested increases from 33-47 percent with no treatment to 80-93 percent when a treatment is available.…”
Section: Anxietymentioning
confidence: 99%
“…People who anticipated feeling more devastated if they learned they were at risk of developing a serious, but medically actionable, disease were less willing to obtain results of genetic tests [19]. In another study, women who anticipated greater stress if they took recommended medication to reduce their high risk of breast cancer were more likely to refuse those medications [20].…”
Section: Similar Sources and Patterns Of Bias When Predicting And Remmentioning
confidence: 99%
“…The longer scale includes two key subscales assessing strengths and values with high reliability; the two items load highly on their respective subscales, and reliability decreases when these particular items are omitted (Harris et al, 2016). Moreover, a version of this two-item index has been used successfully in earlier research examining spontaneous self-affirmation Ferrer et al, 2014). Participants selected one of four response options: strongly agree, somewhat agree, somewhat disagree, strongly disagree.…”
Section: Methodsmentioning
confidence: 99%